Large Zero‐Field Splittings of the Ground Spin State Arising from Antisymmetric Exchange Effects in Heterometallic Triangles1. (15th April 2014) - Magee, Samantha A.; Sproules, Stephen; Barra, Anne‐Laure; Timco, Grigore A.; Chilton, Nicholas F.; Collison, David; Winpenny, Richard E. P.; McInnes, Eric J. L.
Abstract [Ru2Mn(O)(O2CtBu)6(py)3] has an S=5/2 ground state with a very large zero‐field splitting (ZFS) of D=2.9 cm−1, as characterized by EPR spectroscopy at 4–330 GHz. This is far too large to be due to the MnII ion (D <0.2 cm−1), as shown from the Fe2Mn analogue, but can be modeled by antisymmetric exchange effects.